Hacking Humans: The Next National Security Threat - Patrick Neal (The Journal of Intelligence, Conflict and Warfare)
Dr. Neal’s presentation focused on the immediate need for the security environment to focus on the moral, ethical, and practical threats emerging from the new hybrid warfare battlefields that are being created due to the expanding use of technological augmentation in humans. As these technologies expand, there are new national security threats facing numerous actors, including individuals, such as a potential ability to manipulate their own bodily data or from civil unrest as society changes; organizations, such as new markets for organized crime to exploit; and states, such as the possibility of another state hijacking augmentation devices in its population. Dr. Neal emphasized the need for the security industry to think ahead and begin to consider preemptive measures before these technologies advance in order to maintain control over their application and mitigate risks.